2012
DOI: 10.6061/clinics/2012(09)11
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori as a potential target for the treatment of central serous chorioretinopathy

Abstract: OBJECTIVES:The objective of this study was to evaluate the relationship between the treatment of Helicobacter pylori gastric infection and changes in best-corrected visual acuity and macular detachment in patients with chronic central serous chorioretinopathy.METHODS:Seventeen patients diagnosed with central serous chorioretinopathy were examined for gastric infection with Helicobacter pylori using the urease test and gastric biopsy. Helicobacter pylori-positive patients were treated with the appropriate medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Several studies also reported a high prevalence of Helicobacter pylori infection in CSCR patients (Ahnoux-Zabsonre et al, 2004;Cotticelli et al, 2006;Giusti, 2001;Mateo-Montoya and MaugetFaÿse, 2014;Mauget-Faÿsse et al, 2002;Roshani et al, 2014). H. pylori-dependent immune mechanism and molecular mimicry between pathogenic antigens and host proteins (Giusti, 2004) has been hypothesized but additional studies are needed to confirm the relationship between CSCR and H. pylori, and the benefit of H. pylori treatment on the course of CSCR, as suggested by some studies (Casella et al, 2012;Dang et al, 2013;Rahbani-Nobar et al, 2011).…”
Section: Gastroesophageal Disordersmentioning
confidence: 91%
“…Several studies also reported a high prevalence of Helicobacter pylori infection in CSCR patients (Ahnoux-Zabsonre et al, 2004;Cotticelli et al, 2006;Giusti, 2001;Mateo-Montoya and MaugetFaÿse, 2014;Mauget-Faÿsse et al, 2002;Roshani et al, 2014). H. pylori-dependent immune mechanism and molecular mimicry between pathogenic antigens and host proteins (Giusti, 2004) has been hypothesized but additional studies are needed to confirm the relationship between CSCR and H. pylori, and the benefit of H. pylori treatment on the course of CSCR, as suggested by some studies (Casella et al, 2012;Dang et al, 2013;Rahbani-Nobar et al, 2011).…”
Section: Gastroesophageal Disordersmentioning
confidence: 91%
“…People referred to as having a type A personality are usually characterized by a highly status-conscious, ambitious and rigidly organized pattern of behavior [57]. Further risk factors that have been proposed include pregnancy, alcohol consumption, untreated hypertension, use of antibiotics, bone marrow or organ transplantation, infection of the respiratory tract and infection with Helicobacter pylori [12,44,58,59,60,61,62,63]. …”
Section: Systemic and Ocular Risk Factorsmentioning
confidence: 99%
“…Peptic ulcer was highly correlated with CSR in our study. [16][17][18][19][20] Recent studies have shown that H. pylori infection may be a systemic disease, in addition to peptic ulcer disease, associated with gastric cancer, MALT lymphoma, 21,22 and abnormal gastroesophageal reflux. Abnormal gastroesophageal reflex, such as peptic ulcer disease, which is also one of the complications of Helicobacter pylori infection, has been noted to be associated with CSR.…”
Section: Discussionmentioning
confidence: 99%